2004
DOI: 10.1016/s0014-5793(04)00189-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol diet‐induced hyperlipidemia influences gene expression pattern of rat hearts: a DNA microarray study

Abstract: To pro¢le gene expression patterns involved in the direct myocardial e¡ect of cholesterol-enriched diet-induced hyperlipidemia, we monitored global gene expression changes by DNA microarray analysis of 3200 genes in rat hearts. Twentysix genes exhibited signi¢cant up-regulation and 25 showed down-regulation in hearts of rats fed a 2% cholesterol-enriched diet for 8 weeks as compared to age-matched controls. The expression changes of 12 selected genes were also assessed by real-time quantitative polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 54 publications
9
45
2
Order By: Relevance
“…The increase in relative heart weight of HCD-fed compared with control rats could be attributed to the addition of fibrous tissue around the blood vessels and the fibrotic changes in the cardiac myocytes that was evident by the expression of ASMA. Puskas et al [46] explained the increase in heart weight as a response to a cholesterol diet and the accumulation of intracellular lipids in cardiomyocytes. The latter was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in relative heart weight of HCD-fed compared with control rats could be attributed to the addition of fibrous tissue around the blood vessels and the fibrotic changes in the cardiac myocytes that was evident by the expression of ASMA. Puskas et al [46] explained the increase in heart weight as a response to a cholesterol diet and the accumulation of intracellular lipids in cardiomyocytes. The latter was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported alterations in the structural and functional properties of the myocardium in response to HCD [2, 28,46]. Wittenstein et al [57] showed that hyperlipidaemia induces oxidative stress, which plays a key role in atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebellar cells grown in cell culture with cholesterol produced neurodegeneration as indicated by altered morphology, less synaptic connections, and cell shrinkage as compared to normal cells [28]. Cholesterol-enriched diet caused intracellular lipid accumulation and several alterations in the structural and functional properties of the other organs as myocardium [29]. The numerous dense bodies were degenerating mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Hearts were excised, mounted on the Langendorff apparatus and perfused. Despite of several studies employing Langendorff perfusion in rat hearts Puskás et al, 2004), still very little is known about the gene expression pattern of the heart in response to ischemiareperfusion after different periods of time. Without the knowledge of gene expression changes at mRNA and protein levels in the perfused heart, it is difficult to define specific controls and these variations could alter the results of different studies.…”
Section: Introductionmentioning
confidence: 99%